Outgassing from Open and Closed Magma Foams - von Aulock, Felix W.; Kennedy, Ben M.; Maksimenko, Anton; Wadsworth, Fabian B.; Lavallée, Yan (Frontiers in Earth Science, 2017)
During magma ascent, bubbles nucleate, grow, coalesce, and form a variably permeable porous network. The volcanic system opens and closes as bubble walls reorganize, seal or fail. In this contribution we cause obsidian to nucleate and grow bubbles to high gas volume fraction at atmospheric pressure by heating samples to 950 ºC for different times and we image the growth through a furnace. Following the experiment, we imaged the internal pore structure of selected samples in 3D and then dissected for analysis of textures and dissolved water content remnant in the glass. We demonstrate that in these high viscosity systems, during foaming and subsequent foam-maturation, bubbles near a free surface resorb via diffusion to produce an impermeable skin of melt around a foam. The skin thickens nonlinearly through time. The water concentrations at the outer and inner skin margins reflect the solubility of water in the melt at the partial pressure of water in atmospheric and water-rich bubble conditions, respectively. In this regime, mass transfer of water out of the system is diffusion limited and the sample shrinks slowly. In a second set of experiments in which we polished off the skin of the foamed samples and placed them back in the furnace, we observe rapid sample contraction and collapse of the connected pore network under surface tension as the system efficiently outgasses. In this regime, mass transfer of water is permeability limited. The mechanisms described here are relevant to the evolution of pore network heterogeneity in permeable magmas. We conclude that diffusion-driven skin formation can efficiently seal connectivity in foams. When rupture of melt film around gas bubbles (i.e. skin removal) occurs, then rapid outgassing and consequent foam collapse modulate gas pressurisation in the vesiculated magma.